ADVERSE DRUG REACTIONS AND INTERACTIONS OF NSAIDs IN GENERAL CARE HOSPITAL - P.Maheshwari; Praveen.D; V.RAVICHANDIRAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The main aim is to evaluate the Pharmacological aspects of theusage of NSAIDs in a multi-specialty tertiary care hospital. The secondary objectives are to obtain the extent of usage of NSAIDs in the hospital, to prevent inappropriate use of NSAIDs, to analyze Cost effectiveness as continuity of work done by Maheshwariet.al[1]. Method: The study was carried out in multi-specialty hospital. Specially prepared proforma were been designed for the collection of the data. NSAIDs are most commonly prescribed as twice daily dosing. Results:The most commonly prescribed was ketorolac with twice daily dosing followed by diclofenac with twice daily dosing. 264 prescriptions(58.53) had shown potential drug interactions with NSAIDs. The gastroprotective agents that are given along with NSAIDs are H2 blockers were the most commonly prescribed drugs given in 299 patients (66.2%). Conclusion:Drug use problems are common and have significant clinical and economic implications.It is important to remember that most adverse drug reactions would subside once the offending agent was discontinued or its dose reduced. Key Words: NSAIDs, Drug interactions, analgesics